Inflation levels and (in)attention - Anat Bracha; Jenny Tang (Federal Reserve Bank of Boston, 2022)
Inflation expectations are key determinants of economic activity and are central to the current policy debate about whether inflation expectations will remain anchored in the face of recent pandemic-related increases in inflation. This paper explores evidence of inattention by constructing two different measures of consumers' inattention and documents greater inattention when inflation is low. This suggests that there is indeed a risk of an acceleration in the increases in inflation expectations if actual inflation remains high.
Keywords: D80; E31; E70; 330; inattention; inflation expectations; expectation anchoring